2017
DOI: 10.1371/journal.pone.0188572
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting foveal avascular zone in healthy eyes: An examination using swept-source optical coherence tomography angiography

Abstract: ObjectiveTo examine factors affecting foveal avascular zone (FAZ) area in healthy eyes using swept-source optical coherence tomography angiography (OCTA).MethodsThis prospective, cross-sectional study included 144 eyes of 144 individuals (77 women, 67 men) with a best corrected visual acuity of at least 20/20 and no history of ocular disorders. The area of the superficial FAZ was assessed using OCTA. Age, gender, central retinal thickness (CRT), retinal vascular density, refractive error, and axial length were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
55
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 42 publications
13
55
5
1
Order By: Relevance
“…Hence, we decided to enrol participants aged more than 54 (Fujiwara et al. ). However, a study on Chinese population showed that the FAZ area is larger in women than in men (man mean, 0.42 mm 2 ; woman mean, 0.52 mm 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, we decided to enrol participants aged more than 54 (Fujiwara et al. ). However, a study on Chinese population showed that the FAZ area is larger in women than in men (man mean, 0.42 mm 2 ; woman mean, 0.52 mm 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The age cut‐off was chosen based on results from a study by Fujiwara et al. (). The measurement was performed automatically by the software in the superficial layers of the retina.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another fact that should be highlighted is the occurrence of variation of retinal capillary density and age-related FAZ dimensions [12,13], highlighting the importance of new findings from OCT-A. This has been reported in other ischemic diseases, such as diabetic retinopathies [11,14,18,19] and sickle cell disease [20,21], in addition to glaucoma [22], with possible involvement at the level of the deep plexus, in addition to the histological variation found in this plexus, with greater distancing of the fovea and increased dimensions compared to the superficial plexus [23]. However, such enlargement is not easily interpreted, since there is variation in the size of this area also in the general population, since in a single individual this measurement can usually be large or abnormally increased.…”
Section: Discussionmentioning
confidence: 68%
“…CRT has been known to be associated with FAZ area [16]. We addressed the association between PVD and CRT that was defined as the mean retinal thickness within 1mm ETDRS circle on macular thickness map.…”
Section: Pvd Stage and Central Retinal Thickness (Crt)mentioning
confidence: 99%